Managing country risk a practitioner's guide to effective border risk analysis - Wagner, Daniel (CRC Press, Taylor & Francis Group, 2012)
"What would you do if a law that enabled your investment to operate successfully abroad had just been changed, and your business could no longer operate profitably there? Imagine exporting goods to a government buyer only to discover after the fact that your home country, or the United Nations, has just imposed an embargo on that country. An unexpected resignation, a terrorist act, or a currency collapse can instantaneously transform the political and economic landscape of a country or region, and with that, what seemed like a good business decision can quickly become a disaster. Managing Country Risk: A Practitioner's Guide to Effective Cross-Border Risk Analysis explains how to identify and manage the plethora of risks associated with conducting business abroad.
Keywords: BUSINESS & ECONOMICS / Finance; Country risk; Economic forecasting; Investments, Foreign; Wirtschaft; Risikoanalyse; Länderrating; Länderrisiko; Welt